Paròdia sobre paròdia. C. A. Jordana reescrit per Mercè Rodoreda - Mir, Catalina (Studia Romanica Posnaniensia, 2021)
This paper proposes a reinterpretation of plot parallelisms between El collar de la Núria (1927), by C. A. Jordana, and Crim (1936), by Mercè Rodoreda. The comparative analysis aims to show how Crim, in addition to working as a parody of the principles of the detective story, can be read as a parody of an earlier parody of the same genre – that is, the text by Jordana. This rewriting exercise strengthens the hypertextual link between these two novels and results in what we may call, following the terminology by Gérard Genette, a hyperparody.